Model Pemberdayaan Sentra Pisang berbasis Kearifan lokal dan Modal Sosial di Kabupaten Karanganyar, Jawa Tengah - Wibowo, Agung; Lestari, Eny; Rahayu, Paramita (Jurnal Penyuluhan, 2022)
Jenawi District is the largest supplier of bananas in Karanganyar Regency, in the process of empowering it to become a banana center based on local wisdom and social capital. This study aims to analyze local wisdom and social capital that play an important role in the empowerment of banana centers. This study chose an area in Menjing Village in Jenawi District, Karanganyar Regency, with the consideration that this area is the largest banana producer in Karanganyar Regency and has won first place in the best banana exhibition in Central Java province. This study adheres to the phenomenology paradigm with qualitative methods. This study uses a case study, which is an empirical inquiry investigating the strength of the values ​​of social capital and local wisdom in line with the empowerment of banana centers. The results showed that the values ​​of local wisdom and social capital of the community as a determinant of the success of the banana center empowerment process. This local wisdom is shown in the selection of plant seeds, banana cultivation, harvesting, preservation of local varieties, and maintaining land fertility. While the social capital entity in this study is seen from the aspect of participation in a network, reciprocity, trust, values, norms, solidarity, mutual cooperation, helping those in the local community. Local wisdom and social capital are the basis for developing a model for center empowerment.